DIGITAL CONTENT MARKETING DEVELOPMENT WITH A LEVEL UP STRATEGY FOR MSME’s IN INDONESIA “FROM LOCAL TO GLOBAL” - Wijaya, Carissa Vienna; Putri, Angely Olivia; Wijaya, Septihani Michella; Wijaya, Andi (Graduate Program of Universitas Tarumanagara, 2024)
Small and Medium Enterprises (MSMEs) in Indonesia seem to be experiencing challenges due to the rise of imported products circulating in the Indonesian market. However, the quality of MSME products is inconsistent. Not many buy local products or brands. Not all MSMEs in Indonesia have been digitized, which is why the development of digital marketing content with a level up strategy for MSMEs is still weak. We propose a Show with MSMEs strategy